Cyto-immuno-therapy for Cancer: a pathway elicited by tumor-targeted, cytotoxic drug-packaged bacterially derived nanocells (2020)
Immunotherapy has emerged as a powerful new chapter in the fight against cancer. However, it has yet to reach its full potential due in part to the complexity of the cancer immune response. We demonstrate that tumor-targeting EDV nanocells function as an immunotherapeutic by delivering a cytotoxin in conjunction with activation of the immune system. These nanocells polarize M1 macrophages and activate NK cells concurrently producing a Th1 cytokine response resulting in potent antitumor function. Dendritic cell maturation and antigen presentation follows, which generates tumor-specific CD8+ T cells, conferring prolonged tumor remission. The combination of cytotoxin delivery and activation of innate and adaptive antitumor immune responses results in a potent cyto-immunotherapeutic with potential in clinical oncology.